Seasonal Incidence of Diabetes Mellitus. Issue 5671 (13th September 1969) - Gamble, D. R.; Taylor, K. W.
Abstract : A seasonal incidence in the onset of insulin-dependent diabetes in patients under 30 years of age has been suggested from the analysis of data derived from the clinic registers of two diabetic clinics. The increased incidence occurred in summer, autumn, and winter, with a peak in the autumn. A significant variation in annual totals of new cases of diabetes seen could not be demonstrated or excluded, but the pattern of the variation present showed significant positive correlation with the annual prevalence data for Coxsackie virus type B4, but not for other types of virus infection.